(untitled) (Research, Society and Development, 2022)
Objective: to map the clinical profile of newborns and children who had COVID-19. Methods: scoping review, developed based on the method proposed by the Joanna Briggs Institute. The search was carried out in four databases in order to answer the question: What clinical profile of newborns and children who had COVID-19? The extracted data were analyzed in an Excel® spreadsheet. Results: the final sample consisted of 15 studies. There was a predominance of observational cohort studies, published in Asia, Europe and North America, in English and in the year 2020. The most common manifestations were: fever, cough, headache and diarrhea, with mechanical ventilation as the most used device. Ground-glass opacity, lymphopenia, leukopenia and elevated C-reactive protein were the most frequent findings. Most of the population had hospital discharge as an outcome. Conclusion: there is a need to invest in research in this area so that the clinical profile of this population can be more accurately traced in different contexts, so that adequate care can be instituted.